The Application of Intradialytic Stretching Exercise On Restless Legs Syndrome (RLS) Scale in Hemodialysis Patients: Literature Review - Ricky Zainuddin; Ekayanti Hafidah Ahmad; Fitriani Sangkala; Ardiyanto Muslim (Universitas STRADA Indonesia, 2021)
One complaint that is often experienced by patients during hemodialysis is RLS.This is because the implementation of dialysis takes 3-5hours a day or 2to 3times every week.To overcome these problems,intradialytic stretching exercise can be done in the first hour the patient underwent hemodialysis.Aims:To analyze the effect of the application of intradialytic stretching exercise on the scale of RLS in patients undergoing hemodialysis.Method:This research explores quantitative evidence published in electronic databases such as Pubmed and Google Scholar.Using a search strategy,we identified 12articles that were relevant to the purpose of the study, and 3articles were included in the final analysis.Results:We can see a significant effect on the decrease in the scale of RLS in the group, given the intervention compared to the control group.Conclusion:Research results from several articles in this review literature show that the Intradialysis Stretching Exercise is proven to be effective in reducing the RLS scale in patients undergoing hemodialysis.